Dose Optimization of Colistin: A Systematic Review - Haseeb, Abdul; Faidah, Hani Saleh; Alghamdi, Saleh; Alotaibi, Amal F.; Elrggal, Mahmoud Essam; Mahrous, Ahmad Jamal; Almarzoky Abuhussain, Safa S.; Obaid, Najla A.; Algethamy, Manal; AlQarni, Abdullmoin; Khogeer, Asim A.; Saleem, Zikria; et al. (Antibiotics (Basel), 2021)
Colistin is considered a last treatment option for multi-drug and extensively resistant Gram-negative infections. We aimed to assess the available data on the dosing strategy of colistin. A systematic review was performed to identify all published studies on the dose optimization of colistin. Grey literature and electronic databases were searched. Data were collected in a specified form and the quality of the included articles was then assessed using the Newcastle-Ottawa scale for cohort studies, the Cochrane bias tool for randomized clinical trials (RCT), and the Joanna Briggs Institute (JBI) critical checklist for case reports. A total of 19 studies were included, of which 16 were cohort studies, one was a RCT, and two were case reports. A total of 18 studies proposed a dosing regimen for adults, while only one study proposed a dosing schedule for pediatric populations. As per the available evidence, a loading dose of 9 million international units (MIU) of colistin followed by a maintenance dose of 4.5 MIU every 12 h was considered the most appropriate dosing strategy to optimize the safety and efficacy of treatment and improve clinical outcomes. This review supports the administration of a loading dose followed by a maintenance dose of colistin in severe and life-threatening multi-drug Gram-negative bacterial infections.